And the winner is... The presence of political slant in the movie production - Selep, Ján (2014)
I study movie studio profit maximization based on an optimization of a political language in the dialogues. I explore the flexibility with which a rational firm slants language of its movies in order to get closer either to a Democratic or a Republican customer. Using computational linguistics I construct vectors of phrase frequency distribution based on a text of almost a decade of U.S. Congress transcripts and 457 randomly chosen movie subtitles. In order to measure distance between the phrase vectors I use chi square statistics and its Monte Carlo approximation. I find no evidence of political slant in movies neither in a movie studio comparison nor for a time-varying comparison of movies in different years. In addition I construct a slant index covering level of political language in a movie. Using the index I find no evidence of impact of political language on movie revenues.